2019
DOI: 10.1002/jor.24307
|View full text |Cite
|
Sign up to set email alerts
|

Adipose‐Derived Stromal Vascular Fraction and Cultured Stromal Cells as Trophic Mediators for Tendon Healing

Abstract: Adipose‐derived stromal vascular fraction (SVF) is a heterogeneous population of cells that yields a homogeneous population of plastic‐adherent adipose tissue‐derived stromal cells (ASC) when culture‐expanded. SVF and ASC have been used clinically to improve tendon healing, yet their mechanism of action is not fully elucidated. The objective of this study was to investigate the potential for ASC to act as trophic mediators for tendon healing. Flexor digitorum superficialis tendons and adipose tissue were harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 50 publications
(136 reference statements)
0
24
0
1
Order By: Relevance
“…The discrepancy between the results described in literature and those reported in the present study is probably due to the different sources of TCs and to the inflammatory protocol. Since adipose-derived MSCs are known to produce trophic mediator-specific for TCs [49], a slight reduction of SCX expression was observed when TCs were cocultured with μ FAT in basal conditions, and a downregulation of this marker have been already reported by other authors after TCs-MSCs coculture [34]. These observations suggest that μ FAT (or MSCs) trophic action on TCs may be independent of SCX upregulation.…”
Section: Discussionmentioning
confidence: 57%
“…The discrepancy between the results described in literature and those reported in the present study is probably due to the different sources of TCs and to the inflammatory protocol. Since adipose-derived MSCs are known to produce trophic mediator-specific for TCs [49], a slight reduction of SCX expression was observed when TCs were cocultured with μ FAT in basal conditions, and a downregulation of this marker have been already reported by other authors after TCs-MSCs coculture [34]. These observations suggest that μ FAT (or MSCs) trophic action on TCs may be independent of SCX upregulation.…”
Section: Discussionmentioning
confidence: 57%
“…In contrast, expansion of ASCs in vitro may be associated with risks such as possible loss of stemness or cell transformation [29][30][31]. On the other hand, recent studies on culture systems and animal models indicated non-inferiority or even superiority of UA-ADRCs over ASCs in, for example, tendon healing [32], bone regeneration [33] and rescuing heart function after acute myocardial infarction [34] (see also [13]).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, it contains a cell population at its surface that resembles those lining the synovium, being responsible for the production of HA and PRG4 in joint fluid. Secondly, the autocrine properties of adipose tissue with its resident multipotent stromal cells can serve as a source of inflammatory mediators, such as interleukins, nitric oxide, chemokines, and prostaglandins [ 56 ]. Thirdly, this multipotent cell population has been described in post-injury responses, including cellular proliferation, HA accumulation, and fibrotic remodeling, as well as having a potential for neo-vascularization [ 57 ], chondrogenesis [ 58 ], or modulation of pain responses [ 59 ].…”
Section: Discussionmentioning
confidence: 99%